The introduction of exotic tree species with special reference to Pinus contorta in northern Sweden : review and background - Karlman, Margareta (1981)
The background to the large-scale planting of Pinus contorta in northern Sweden is reviewed with an account of the distribution and characteristics of Pinus contorta within its natural range in western North America. The Swedish Forestry Act of 1979 places restrictions on the planting programme of Pinus contorta. The threats to successful planting of exotics are discussed in relation to the historical background. Attention is also drawn to parasitic fungi which are infecting Pinus contorta in western Canada, and to the potential threat they represent to the indigenous Pinus sylvestris in Sweden.